Embolization coils: Materials, designs, and future directions - Jiaywei Tsauo (International Journal of Gastrointestinal Intervention)
Embolization coils are among the most commonly used embolic agents for transcatheter arterial embolization in gastrointestinal bleeding. The materials and designs of these coils influence key performance characteristics, such as stiffness, radiopacity, and thrombogenicity. Each coil type, including fibered, hydrogel, and bare coils, possesses distinct advantages and limitations. However, comparative studies directly evaluating different coil types or the same type from different manufacturers remain scarce. Consequently, operators require a thorough understanding of coil technology to anticipate coil performance and select the optimal coil for each clinical scenario. This short review discusses the materials and designs of embolization coils and highlights future directions in their technological development and clinical application.